Evaluasi Kemampuan Menulis Pantun pada Siswa Kelas VII SMP Negeri 1 Kepenuhan Hulu - Yunhelmi, Yunhelmi; Rahayu, Sri (UIR Press, 2024)
This study describes how students' abilities in writing rhymes. Writing activity is a process of one's activities in pouring ideas or thoughts, and feelings into a written language with the development of a mindset in the form of literature. The author's reason for taking this research is to find out how the level of students' ability in writing rhymes. The purpose of this study was to describe, find out, improve students' ability to write rhymes and find out what causes the lack of ability to write rhymes for class VII students at SMP N 1 Kepenuhan Hulu for the 2022/2023 academic year using a learning model approach to students. This research uses a quantitative descriptive method with this type of classroom action research. So the researcher can conclude that the Ability to Write Pantun for Class VII Students of SMA Negeri 1 Kepenuhan Hulu is in a very good category. This can be seen from the acquisition of an average student test score of 94.82 in the interval score range (91-95) with a conversion result of 3.66 or with very good criteria. Most students have understood how to write rhymes according to the conditions. Thus the ability to write rhymes for class VII students of SMP Negeri 1 Kepenuhan Hulu for the 2022/2023 academic year is in the very good category (94.82).